Team Approach for the Management of Amelogenesis Imperfecta - Shakya, Sonika; Pradhan, Shaili; Alam, Munna (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Amelogenesis imperfecta is a developmental disturbance that interferes with normal enamel formation in the absence of a systemic disorder. This case report describes a multidisciplinary team approach for the oral rehabilitation of a young adult patient diagnosed with hypocalcified amelogenesis imperfecta with anterior single tooth crossbite. The specific objectives of this treatment were to enhance esthetics, eliminate tooth sensitivity and restore masticatory function. Treatment included maintenance of gingival health, correction of crossbite, surgical crown lengthening of the maxillary and mandibular posterior teeth and placement of full mouth metal-ceramic crowns. The patient was highly satisfied with the aesthetic and functional outcome of the treatment.